A rare case of drug-induced agranulocytosis: A challenging diagnosis andmanagement approach (Indian Journal of Case Reports, 2024)
Agranulocytosis is a severe adverse drug reaction characterized by a significant decrease in the number of neutrophils, making patients highly susceptible to infections. I present a rare case of drug-induced agranulocytosis in a 45-year-old male patient who presented with a sudden onset of fever, sore throat, and severe fatigue. Infectious and autoimmune etiologies were ruled out by thorough examinations. A thorough medication history indicated that a new drug for the treatment of hypertension had just been started (chlorthalidone). The patient was immediately placed on broad-spectrum antibiotics and granulocyte colony-stimulating factor after the medication was rapidly stopped. The patient’s neutrophil count gradually increased with prompt management, and he displayed clinical improvement. This instance emphasizes the value of prompt diagnosis and treatment of drug-induced agranulocytosis to avert potentially fatal consequences.